2023
DOI: 10.1037/edu0000761
|View full text |Cite
|
Sign up to set email alerts
|

The interconnected development of depressive symptoms and school functioning from mid-adolescence to early adulthood: A piecewise growth mixture analysis.

Abstract: This study seeks to identify profiles of depressive symptoms trajectories among a sample of 2,696 Finnish students (56.8% female), followed from 13–14 to 18–19 years old. Piecewise growth mixture analyses identified 5 trajectories: Low Stabilizing (6.20%), Mild Increasing (47.90%), Moderate Stabilizing (36.82%), Low Increasing (3.62%), and High Stable (5.46%). Relative to boys, girls experienced more problematic depressive symptoms trajectories. The study also assesses whether achievement goals growth predicts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 121 publications
1
5
1
Order By: Relevance
“…Consistent with previous findings by Ezpeleta et al (2020) and Olivier et al (2022), which revealed a low trajectory and a high trajectory of depression symptoms, the present study also identified two trajectories of depression symptoms during the transition into early adolescence, which comprised the trajectory of low depression symptoms (85.6%) and the trajectory of high depression symptoms (14.4%). Although the trajectories were not stable (decreased from T1 to T2 and increased from T2 to T3) across the transition into early adolescence, the general level of depression symptoms (low and high) remained constant across the period, which was consistent with previous studies (Ezpeleta et al, 2020;Olivier et al, 2022).…”
Section: Similarity With Previous Findingssupporting
confidence: 91%
“…Consistent with previous findings by Ezpeleta et al (2020) and Olivier et al (2022), which revealed a low trajectory and a high trajectory of depression symptoms, the present study also identified two trajectories of depression symptoms during the transition into early adolescence, which comprised the trajectory of low depression symptoms (85.6%) and the trajectory of high depression symptoms (14.4%). Although the trajectories were not stable (decreased from T1 to T2 and increased from T2 to T3) across the transition into early adolescence, the general level of depression symptoms (low and high) remained constant across the period, which was consistent with previous studies (Ezpeleta et al, 2020;Olivier et al, 2022).…”
Section: Similarity With Previous Findingssupporting
confidence: 91%
“…Inasmuch as they doubt that their lives are going well, they will likely be less action-oriented and display fewer behaviors that would otherwise allow them to achieve success in various domains. Depressive symptomatology thus creates conditions that prevent positive human potential, motivation, and persistence, hampering performance and potentially educational attainment as well (Berndt et al, 2000; Fletcher, 2010; Olivier et al, 2023).…”
Section: Mental Health Gender and Educational Attainment At Various D...mentioning
confidence: 99%
“…In a Finnish study of young people, a group characterized by low climate change-related well-being and high rates of PEB had significantly more depressive symptoms and lower self-esteem than the other participants (Veijonaho & Salmela-Aro, 2022). Overall, the declining well-being of students at all levels of education has been a concern in Finland (Olivier et al, 2023; Read et al, 2022). More research is therefore needed on all aspects that affect the overall well-being of young people.…”
Section: Climate Change Distress Pro-environmental Behavior and Gener...mentioning
confidence: 99%